EFECTO DE FERTILIZANTES SOBRE LA PRODUCCIÓN DE BIOMASA Y PARÁMETROS DE CALIDAD EN PASTOS HERBÁCEOS DE DEHESA DESPUÉS DE TRES AÑOS CONTINUADOS DE APLICACIÓN - SANTAMARÍA, O.; Poblaciones, M. J.; Olea, L.; Rodrigo, S.; VIGUERA, F. J.; GARCÍA-WHITE, T. (PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes, 2010)
Dehesa is an agrosilvopastoral system widespread in southwestern Iberian Peninsula. Natural pastures, which are the main source, could be improved by using a proper fertilization, among other practices. With the aim of evaluating the effect of different fertilizers on biomass production and sev- eral nutritive value parameters (crude protein, fiber and lignin) of the pasture in comparison with the traditionally used superphosphate, a study was initiated in 2006/07. In the present communication, the third-year-results (2008/09) are presented. The study was carried out in a dehesa located in Extre- madura, in two areas: one with natural pastures and other with sown pastures. Eight surface-broadcast fertilization treatments were done in autumn. Two grazing periods were simulated by cutting the pas- ture in middle-spring and late-spring. Although no statistical differences were found among treat- ments, fertilizers tended to increase biomass production in comparison to the non-fertilized control; in some cases (treatment M1in the sown pasture) increments were close to 50%. Regarding the nutritive value, treatment T2 (the highest doses of Thomaskali fertilizer, 300 kg·ha-1) produced biomass with the significant highest protein content
The following values have no corresponding Zotero field: periodical: PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes pub-location: Zamora
Keywords: crude protein; fiber; Lignin; natural pasture; sown pasture

The impact of grazing on forage quality of the herbaceous vegetation in the Mamora cork oak forest, Morocco - Alami, M Mejjati; Bedell, T E; Sharrow, S H; Berkat, O (African Journal of Range & Forage Science, 1997)
This research was conducted in the Mamora cork oak forest of Morocco to describe the impacts of sheep grazing (no use, 35% use, 70% use) in March, April, May and June of 1987 and 1988 on seasonal changes in forage quality of the herbaceous vegetation. The study showed that trends in herbage quality were related mainly to plant maturity. As more species mature, forage quality declines and falls below animal nutritional requirements, especially for young animals. With declining forage quality, the manager has the option of moving stock to areas of less-mature forage, supplementing the forage or modifying the demand placed upon it.
doi: 10.1080/10220119.1997.9647913
Keywords: crude protein; IVOMD; Mediterranean-type climate; minerals; time of grazing

The impact of grazing on forage quality of the herbaceous vegetation in the Mamora cork oak forest, Morocco - Alami, M. Mejjati; Bedell, T. E.; Sharrow, S. H.; Berkat, O. (African Journal of Range & Forage Science, 1997)
This research was conducted in the Mamora cork oak forest of Morocco to describe the impacts of sheep grazing (no use, 35% use, 70% use) in March, April, May and June of 1987 and 1988 on seasonal changes in forage quality of the herbaceous vegetation. The study showed that trends in herbage quality were related mainly to plant maturity. As more species mature, forage quality declines and falls below animal nutritional requirements, especially for young animals. With declining forage quality, the manager has the option of moving stock to areas of less-mature forage, supplementing the forage or modifying the demand placed upon it.
doi: 10.1080/10220119.1997.9647913doi: 10.1080/10220119.1997.9647913The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: crude protein; IVOMD; Mediterranean-type climate; minerals; time of grazing